DEVELOPMENT OF SUSTAINABLE, ALKALI-ACTIVATED BINDERS FOR CONSTRUCTION - Alelweet, Omar (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2023)
This work contributes to the design and production of alkali-activated materials (AAMs) of lower environmental impact than Portland cement (PC) products. AAM binders result from the reaction of an activator and a precursor. They do not require clinkering and can be produced at ambient temperature using waste precursors as the principal constituent. Hence, they reduce energy consumption, CO2 emissions, and the use of unrenewable resources for their production. Aluminosilicate precursors not investigated to date such as Saudi Arabian red mud (RM) and bauxite are studied. Their particle size, specific surface area, water demand, carbon content, composition and amorphousness are studied, and their reactivity measured with the Chapelle test, setting times, conductivity, mechanical index and microscopy. The quality and durability of AAMs made with these, FA and GGBS precursors, activated with NaOH and Na2SiO3 are investigated to optimize the mix design for a given precursor. All the precursors are pozzolanic and successfully activate with alkali solutions forming AAMs. The FA and GGBS comply with standard requirements for use as PC replacement. GGBS has excellent quality being highly reactive, basic (CaO+MgO/SiO2=1.56) and amorphous, with ratios (CaO/SiO2=1.41; SiO2/Al2O3=0.34) suitable for alkali activation. The RM is reactive due to its layered phases of high surface area (gibbsite and boehmite inherited from the parent bauxite), and its zeolite/feldepathoid phases (cancrinite, chantalite and sodalite) formed during the refining (Bayer) process. It is suitable for the production of AA and pozzolanic materials. It has high SiO2 and high alkalinity, the chloride and carbon contents are low and contains no toxic elements. The RM sintered at 300-400?C sets the fastest, combines the most lime and reaches the greatest strength. The RM?s activity is mainly due to the reaction of feldspathoid cancrinite and formation of zeolitic/feldspathoid-based hydrates. The bauxite is highly reactive due to the layered atomic structures of its main components gibbsite, boehmite and kaolinite, which provide high specific surfaces and active hydroxyls that enhance dissolution and subsequent geopolymerization. Calcination, even at 300?C, dehydroxylates kaolinite increasing reactivity. The 550?C bauxite (highest surface area) is the most active initially (hours-2 days) but at later ages, the 700?C -800?C bauxites (highest amorphous alumina content) are the most reactive reaching the greatest strengths. Some of the AAMs are fit for structural purposes, having strengths and durability superior to their CEM II equivalents at a much lower environmental impact. In AA GGBS materials, the right activator procured similar strength, but much lower embodied energy (EE) and carbon emissions (ECO2) -39.51 % and 78.57 % lower respectively-, than equivalent CEM II materials. The (Na2SiO3+NaOH activated) GGBS materials show the greatest strengths and microstructure. When cured at 60?C, they develop hydrogarnet?gehlenite cements responsible for their high strength (94 MPa at 270 days). The materials cured at 20?C are suitable for many applications. Curing at 60?C enhances early strength (3-7 d.), but ultimate strength (28-270 d.) can lower. The rheology and setting times of AA GGBS materials are within practical limits, and cracking is hindered by the high calcium in the slag. The GGBS is too reactive (too fine and amorphous) for a successful activation with high hydroxide concentration: the best activator is Na2SiO3 combined with low molarity-6M- hydroxide. Some of the AA materials made with RM alone reach significant flexural (5 MPa) and compressive strength (7 MPa), but failed during cycling, being particularly vulnerable to frost. Replacing RM with FA increased strength and durability, and GGBS substitution enhanced quality further. When blended with FA/GGBS, N-A-S-H hydrates are common which improve strength and microstructure. The best AA RM materials (50%GGBS) show the highest density, shortest setting time, greatest strength (39 ? 41 MPa activated with Na2SiO3 / 6M NaOH = 1 and 2.5 respectively), and superior durability than their CEM II equivalents, due to the high-Ca forming strong C-S-H/C-A-S-H cements. The RM needs silica and NaOH in the activator to dissolve and form a strong geopolymer structure: Na2SiO3 alone lowers strength and undermines the structure. The DOE (Design of Experiments) proved suitable to predict optimum mixes for AA bauxite materials in the range studied, and it validated the experimental methods. Bauxite creates outstanding AAMs (compressive strength -CS = 72-90 MPa) of low environmental impact. The bauxite alone produced quality geopolymers (CS=35MPa). Replacing bauxite with FA or GGBS enhances strength and density lowering porosity, and the effect is more pronounced with increasing replacement. Cementing geopolymers are scarce in the AA bauxite, but with FA/ GGBS, the main cementing phase in a low-Ca, aluminate?silicate gel with some sodium substitution. The best materials include 50%GGBS, activated with Na2SiO3/8M NaOH=1, cured at 60?C. A formulation that reached 90 MPa -90 d- and 72 MPa -28 d- and agrees with the optimum mix forecasted by the DOE. The best experimental bauxite and bauxite-FA materials are cured at 20?C and activated with high silica (Na2SiO3/NaOH=3) and medium molarity (8M NaOH). However, the DOE forecast optimum mixes activated with less silica (Na2SiO3/NaOH=2) and higher molarity (NaOH 10M) -with 50%FA, cured at 20?C. The activator must fit the precursor: an excessive activator content or too high concentration escalates environmental impact simultaneously lowering strength and undermining microstructure. Using higher impact precursors such as GGBS, offsets impact on account of increasing the strength and durability in the resultant AAMs. Pyro-processing precursors reports great strength increase with low rise in environmental impact: sintering bauxite at 800oC slightly raised environmental impact but doubled strength. In the AAMs developed, even the highest impacts (EE=0.62-0.64 MJ/kg which correspond with strengths of 15-22 MPa) are small when compared with those of common construction materials.
APPROVED
Keywords: Reactivity; water demand; alkali-activated materials; fly ash; GGBS; red mud; bauxite; embodied energy; carbon footprint